Scoping Review of Acute and Preventive Therapies in Cluster Headache and Network Meta-Analysis of Acute Therapies, Subgroup Analysis by Headache Subtype (Episodic and Chronic) - Medrea, Ioana (Université d'Ottawa / University of Ottawa, 2021)
Cluster headache is a primary headache disorder that can be highly disabling. In this thesis we look at the treatment landscape of cluster headache with a scoping review of preventive and acute therapies for cluster headache as identified in randomized controlled trials and two-arm observational studies. We subsequently compare these therapies where data are available using network meta-analysis of randomized trials, and we attempt subgroup analyses again where data are available for acute treatments of episodic and chronic cluster. We identify the ranking of treatments for acute cluster headache, and certain acute therapies that may be beneficial in episodic and chronic cluster headache. Based on our findings, we also identify future directions for cluster headache trials.
Keywords: cluster headache; network meta-analysis